Absence of charge transfer sate enables very low VOC losses in SWCNT: fullerene solar cells - Classen, Andrej; Graf, Arko; Brohmann, Maximilian; Berger, Felix J.; Zaumseil, Jana (Advanced energy materials, 2019)
Current state-of-the-art organic solar cells (OSCs) still suffer from high losses of open-circuit voltage (VOC). Conventional polymer:fullerene solar cells usually exhibit bandgap to VOC losses greater than 0.8 V. Here a detailed investigation of VOC is presented for solution-processed OSCs based on (6,5) single-walled carbon nanotube (SWCNT): [6,6]-phenyl-C71-butyric acid methyl ester active layers. Considering the very small optical bandgap of only 1.22 eV of (6,5) SWCNTs, a high VOC of 0.59 V leading to a low Egap/q − VOC = 0.63 V loss is observed. The low voltage losses are partly due to the lack of a measurable charge transfer state and partly due to the narrow absorption edge of SWCNTs. Consequently, VOC losses attributed to a broadening of the band edge are very small, resulting in VOC,SQ − VOC,rad = 0.12 V. Interestingly, this loss is mainly caused by minor amounts of SWCNTs with smaller bandgaps as well as (6,5) SWCNT trions, all of which are experimentally well resolved employing Fourier transform photocurrent spectroscopy. In addition, the low losses due to band edge broadening, a very low voltage loss are also found due to nonradiative recombination, ΔVOC,nonrad = 0.26 V, which is exceptional for fullerene-based OSCs.
Published online: November 13, 2018
Gesehen am 10.06.2019